Utility of Maternal 6-Thioguanine Nucleotide Levels in Predicting Neonatal Pancytopenia - Hidehiko Maruyama; Katsuhiko Tada; Takuzo Fujiwara; Kosuke Ota; Misao Kageyama (Thieme Medical Publishers, Inc., 2013)
Abstract An infant with pancytopenia was born to a mother who used the common immunosuppressant azathioprine (AZA). Maternal and neonatal blood levels of 6-thioguanine nucleotides (6TGN; metabolite of AZA) were 1890 and 1480 pmol/8 × 108 red blood cells, respectively. Maternal 6TGN levels could be useful in predicting neonatal pancytopenia.